2016
DOI: 10.1044/2016_aja-16-0034
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Examination of the Effect of Diabetes on Sensory Processing in Older Adults

Abstract: Purpose: The purpose of this article is to examine retrospectively the impact of diabetes mellitus on auditory, visual, and tactile processing in older adults. Method: Fourteen (10.4%) of a sample of 135 older adults self-reported the presence of diabetes mellitus in a study of sensory and cognitive processing across the adult lifespan. In this study, the performance of the subgroup with diabetes on a number of psychophysical sensoryprocessing measures was compared with that of the 121 older adults without dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…Contrary to the results of this study, the VMI of diabetic older adults was significantly lower along with cognitive function (Yun et al, 2013). In a retrospective study (Humes, 2016), sensory processing tasking found differences more sensitively than cognitive function tests comparing the diabetic and nondiabetic older adults. Therefore, with a comfortable reading print size, verification of the difference in VMI between diabetic and nondiabetic older adults needs to be reconfirmed through future studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to the results of this study, the VMI of diabetic older adults was significantly lower along with cognitive function (Yun et al, 2013). In a retrospective study (Humes, 2016), sensory processing tasking found differences more sensitively than cognitive function tests comparing the diabetic and nondiabetic older adults. Therefore, with a comfortable reading print size, verification of the difference in VMI between diabetic and nondiabetic older adults needs to be reconfirmed through future studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Especially, visual-somatosensory integration and motor function could deteriorate in diabetic older adults ( Mahoney et al, 2021 ). Sensory processing tasking could detect differences more sensitively than cognitive function tests between diabetic and nondiabetic older adults ( Humes, 2016 ). MMSE, which is traditionally widely used to measure cognitive function, has limitations in finding such differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation